Unlocking the Power of Employee Engagement: Unveiling the Key Indicators in Public Sector Organizations - Muhammad Yunus; Amril Hans; Andi Ahmad Yani; Sangkala Sangkala; Muhammad Nursadik; Gita Susanti; Muhammad Tang Abdullah; Andi Rahmat Hidayat (Jurnal Manajemen Pelayanan Publik, 2023)
This article proposes to explore the concept of employee engagement in the context of regional government, finding out its antecedents and implications for organizational performance, with a case study on the Provincial Government of South Sulawesi, Indonesia. This study used a quantitative approach with a survey method to collect data from South Sulawesi Provincial Government employees with 3,799 total respondents. This study implies descriptive quantitative analysis methods in analyzing data to find out the variables that contribute to the rigorous concept.  This study analyses six main indicators in measuring the quality of Employee Engagement, namely supervisor evaluation, teamwork, growth opportunities, work-life balance, behavioral fairness, and effective communication. The results showed a high level of Employee Engagement among South Sulawesi provincial government employees, with an average overall percentage of 79.46% and the category "very high."  These results indicate high levels of employee satisfaction and engagement in achieving organizational goals. This research provides important insights into the potential and relevance of Employee Engagement in improving performance and public services in public sector organizations. These findings provide a foundation for public sector organizations to better understand and utilize employee engagement as a key to achieving excellence in public services and achieving overall organizational goals.